(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
English has become one of the world’s dominant languages today, significantly influencing global communication, science, business, and technological development. It has not only become a tool in international cooperation and education but has also become an integral part of society through culture, art and mass media. Learning English is not just an advantage- but it is a fundamental necessity. It is spoken by over 1.5 billion people worldwide.